INTERAKSI ISLAM DENGAN KEBUDAYAAN BANJAR - Abdul Wahab Syakhrani; Muhammad Shaufi; Abdul Hafis Ansyari; Muhammad Riduan (Cross-border, 2023)
The Banjar people are residents (native) of the area around the city of Banjarmasin (the area of the Jingah River, Kuin and Kampung Melayu). This area extends to Martapura City, the capital of Banjar Regency and the surrounding area. Most historians say that 1540 AD was the year in which Islam was officially accepted by the king of the Banjar kingdom, Prince Samudera, who later changed his name to Prince Suriansyah. The entry of Islam in Banjar was through Islamic traders who traded while carrying out da'wah missions.